Tinjauan Hermeneutika Atas Konsep Ketuhanan Ibn Thuffail - Akhmad Jazuli Afandi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2018)
This paper aims to see how far the philosophical thought of the god of Ibn T{ufail. The existence of God and the argument to establish His existence have become an important object in Islamic philosophical studies and its discussion was presented in various ways by Muslim philosophers, among them Ibn T{ufail al-Andalusi. Through the work of Roman Alegorik titled Hay Bin Yaqzan, Ibn T{ufail is trying to present a figure who is looking for God through his sense. Hermeneutic is choosen to analyze the subject and be explained by narative methode. The conclution is Ibn T{ufail's concept of god has a rationalist character. To know the existence of God, a servant can maximize his rational role even without divine guidance. The rationality is supplemented by metaphysical properties.